Trinidad and Tobago : 2004 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Trinidad and Tobago. (IMF Staff Country Reports; Country Report ;, 2005)
This 2004 Article IV Consultation highlights that Trinidad and Tobago's economy, which is endowed with large energy reserves, is experiencing a strong energy sector-based expansion owing to increased output and high international prices. The energy sector already accounts for about 40 percent of GDP, 83 percent of domestic goods exports, and slightly more than 40 percent of government revenue. The balance of payments recorded an increased surplus in 2003, despite large capital outflows, reflecting the strong performance of the energy sector.